2019
DOI: 10.1017/s0047279419000813
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Default Behaviour in Workplace Pensions: Automatic Enrolment in the UK.

Abstract: This article examines the retirement savings behaviour of twenty-five 30-40 years olds automatically enrolled into a workplace pension scheme. Using qualitative interviews, the paper explores the interaction between savings motivation and willingness to adhere to, or deviate from, the pension scheme defaults. Integrating insights from different savings paradigms, including sociological approaches and behavioural economics, the paper highlights how social motives drove willingness to accept enrolment defaults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The interviewees were invited to participate in the study having been identified from responses to a company-wide workplace survey (N3457) designed by the researcher (Robertson-Rose 2016). This survey included a financial literacy test based upon the Organisation for Economic Co-operation and Development (OECD) guidance for measuring financial literacy (OECD 2013) and all the participants obtained an above-average score.…”
Section: Methodsmentioning
confidence: 99%
“…The interviewees were invited to participate in the study having been identified from responses to a company-wide workplace survey (N3457) designed by the researcher (Robertson-Rose 2016). This survey included a financial literacy test based upon the Organisation for Economic Co-operation and Development (OECD) guidance for measuring financial literacy (OECD 2013) and all the participants obtained an above-average score.…”
Section: Methodsmentioning
confidence: 99%
“…Under the opt-out condition, people are more likely to get vaccinated ( Liu et al, 2022 ), accept screening tests for potential diseases ( Bartholomew et al, 2020 ), and choose a healthy diet ( Velema et al, 2018 ). In the organizational context, opt-out approach has also been suggested as an effective intervention to improve employees’ behavior, such as in relation to stand-up working ( Venema et al, 2018 ), pension scheme enrollments ( Thaler and Sunstein, 2008 ; Robertson-Rose, 2021 ), efficiency in energy use ( Brown et al, 2013 ; Egebark and Ekström, 2016 ), and flu vaccination ( Chapman et al, 2010 ). Furthermore, default nudges are easy to implement at a low cost ( Thaler and Sunstein, 2008 ), making them suitable to promote policy support.…”
Section: Introductionmentioning
confidence: 99%